Immunopathological activities of extracellular products of Streptococcus mitis, particularly a superantigenic fraction. - Matsushita, K (1995)
Previously, we prepared extracellular products, fractions F-1 and F-2 of Streptococcus mitis 108, an isolate from the tooth surface of an infant, and showed that F-1 exhibited inflammatory cytokine-inducing activities. In the present study, we present evidence that fraction F-2 induced human T-cell proliferation in the presence of irradiated human peripheral blood mononuclear cells and selectively activated T cells bearing V beta 2 and V beta 5.1 in the T-cell receptor. F-1, on the other hand, stimulated human gingival fibroblasts to support the T-cell proliferation in the same way as human gamma interferon or Prevotella intermedia lipopolysaccharide (LPS). Fraction F-1 also primed gingival fibroblasts to support the production of interleukin-2 and gamma interferon by the T cells upon stimulation with F-2. Human gingival fibroblasts stimulated with fraction F-1, like those stimulated by P. intermedia LPS and human gamma interferon, exhibited human leukocyte antigen (HLA)-DR mRNA expression and cell surface HLA-DR molecules as detected by enzyme-linked immunosorbent assay. An anti-HLA-DR monoclonal antibody inhibited T-cell proliferation in response to F-2, probably through inactivating the accessory function of HLA-DR-bearing fibroblasts. T cells activated with F-2 in the presence of irradiated peripheral blood mononuclear cells exhibited definite cytotoxic effects against fibroblasts and squamous carcinoma cells originating from human oral tissues. These findings are strongly suggestive of an association of extracellular products of viridans streptococci with pathogenesis of oral mucosal diseases, particularly those disorders in gingiva which are accompanied by heavy infiltration of T cells.